Biomarkers of Endothelial, Renal, and Platelet Dysfunction in Stage 5 Chronic Kidney Disease Hemodialysis Patients With Heart Failure. (March 2018) - McMillan, Ryan; Skiadopoulos, Leonidas; Hoppensteadt, Debra; Guler, Nil; Bansal, Vinod; Parasuraman, Ravipresenna; Fareed, Jawed
The aim of this study was to determine the role of endothelial, renal, and inflammatory biomarkers in the pathogenesis of heart failure (HF) in patients with stage 5 chronic kidney disease (CKD5) undergoing maintenance hemodialysis (HD). Plasma levels of biomarkers—kidney injury molecule 1 (KIM-1), N-terminal pro brain natriuretic peptide (NT-proBNP), glycated hemoglobin, neutrophil gelatinase–associated lipocalin, interleukin-18, platelet-derived growth factor, platelet factor 4 (PF4), 25-OH vitamin D, parathyroid hormone (PTH), endothelin, and endocan—were measured in CKD5-HD patients at the Loyola University Ambulatory Dialysis facility. The HF (+) CKD5-HD patients, as compared to HF (−) CKD5-HD patients, exhibited significantly elevated NT-proBNP ( P = .0194) and KIM-1 ( P = .0485). The NT-proBNP in HF (+) CKD5-HD patients was found to correlate with the levels of serum potassium ( P = .023, R = −.39), calcium ( P = .029, R = −.38), and PF4 ( P = .045, R = −.35). The KIM-1 in HF (+) CKD5-HD patients was found to correlate with PTH ( P = .043, R = −.36) and 25-OH vitamin D ( P = .037, R = .36). Elevated plasma NT-proBNP and KIM-1 in CKD5-HD and HF (+) CKD5-HD patients suggest that natriuretic peptides and KIM-1 may contribute to the pathogenesis of HF in CKD5-HD patients.